Pemanfaatan Hasil Pulungan Untuk Meningkatkan Pendapatan Dimasa Pandemi Bagi Pemulung Di TPA Air Dingin - Wati Wati; Sri Rahmadani; Bunga Suci Maharani; Nora Susanti (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The pandemic has changed all orders of life, all levels of society have been affected, including the lives of scavengers who work to collect used waste. Scavengers usually sell all their scavenged products, even though there are types of scavengers that can be used as recycled creations that have a selling value. This service aims to provide an understanding to scavengers on how to recycle scavenged goods to make various creations that have economic value. In line with this service activity, training and coaching for scavenger families will be carried out. The presentation of the material is carried out using lecture and discussion methods, supported by infocus media. The scavenger participants immediately took part in practicing how to make various plastic waste recycling creations with materials that had been prepared by the service team. Through this service, it is hoped that scavengers will gain understanding to develop their potential, gain skills, which eventually become creative and skilled human beings so that they will be able to improve the family's economic condition during the current pandemic.